2019
DOI: 10.1186/s12889-019-7970-z
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in metabolic syndrome in the French West Indies

Abstract: BackgroundObesity and metabolic diseases represent a major health burden in the Caribbean, particularly since a large part of the population is disadvantaged. However, socioeconomic inequalities in chronic diseases are poorly explored in this region. We investigated the association between socioeconomic position and metabolic syndrome (MetS) prevalence and explored the contribution of diet quality to explain this association, among adults in the French West Indies.MethodsThis cross-sectional analysis included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
4
14
1
3
Order By: Relevance
“…However, the use of the illustrated booklet with more than 250 photos, corresponding to 1000 generic foods, served in seven different portion sizes, and the fact that recalls were conducted by trained dietitians have limited the bias. Also, 15% of the subjects were identified as energy underreporters and excluded from the analysis sample: compared with included subjects, the excluded participants were younger, with a higher percentage of unemployed or neveremployed individuals [51]. Finally, some other drivers of the nutrition transition, such as characteristics of the foodscape (neighborhood densities of fast-food outlets or supermarkets) and the food availability, could not be considered in our models.…”
Section: Limitationsmentioning
confidence: 99%
“…However, the use of the illustrated booklet with more than 250 photos, corresponding to 1000 generic foods, served in seven different portion sizes, and the fact that recalls were conducted by trained dietitians have limited the bias. Also, 15% of the subjects were identified as energy underreporters and excluded from the analysis sample: compared with included subjects, the excluded participants were younger, with a higher percentage of unemployed or neveremployed individuals [51]. Finally, some other drivers of the nutrition transition, such as characteristics of the foodscape (neighborhood densities of fast-food outlets or supermarkets) and the food availability, could not be considered in our models.…”
Section: Limitationsmentioning
confidence: 99%
“…× 100), where X is 2, 3, or 4) as done in previous studies [41][42][43]. This method has been shown to result in similar findings as the counterfactual framework approach [43].…”
Section: Statistical Analysesmentioning
confidence: 62%
“…All models were adjusted for the mode of survey completion (paper, internet, phone, or face-to-face) and accounted for the complex survey design through survey weights. The contributions of factors were assessed by comparing the relative risk and odds ratios, and their percentage change (( ), where X is 2, 3, or 4) as done in previous studies [ 41 , 42 , 43 ]. This method has been shown to result in similar findings as the counterfactual framework approach [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis has shown that if the literacy level increase, the chances of developing MetS would be decreased. Evaluating the individuals' educational level showed that this factor was closely related to MetS [14,27]. Using educational platforms can help prevent MetS by increasing people's knowledge, attitude, and as a result, change their practice.…”
Section: Discussionmentioning
confidence: 99%